2014
DOI: 10.1111/ene.12621
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive training in Parkinson's disease reduces cognitive decline in the long term

Abstract: This study gives evidence that cognitive training may be effective to prevent cognitive decline and onset of MCI in PD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 26 publications
(36 reference statements)
0
38
1
8
Order By: Relevance
“…Moreover, the NV group significantly improved more in working memory than MF group. With 1-year follow-up of 45 on 65 original patients (Petrelli et al 2015), researchers concluded that both cognitive trainings yield a stabilization of overall cognitive functions and a reduced risk of developing MCI.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the NV group significantly improved more in working memory than MF group. With 1-year follow-up of 45 on 65 original patients (Petrelli et al 2015), researchers concluded that both cognitive trainings yield a stabilization of overall cognitive functions and a reduced risk of developing MCI.…”
Section: Resultsmentioning
confidence: 99%
“…A recent CT trial involving PD patients without dementia demonstrated that improvements to specific cognitive functions were maintained 1 year following treatment and reduced the risk of developing cognitive impairment . The feasibility of CST for PD patients without dementia has also been demonstrated .…”
Section: Discussionmentioning
confidence: 99%
“…Although recovery can be enhanced by training (Han et al, 2014;Hubbard et al, 2014;Petrelli et al, 2014), there usually remains major functional deficits. Therefore, seeking an effective strategy for axonal regeneration and functional recovery is critical.…”
Section: Introductionmentioning
confidence: 99%